Influence of social support and coping strategies on psychological stress among frontline medical personnel during the Yangbi Earthquake: a cross-sectional analysis - Li, Jiafeng; Ye, Jing; Yang, Xiaolan; Sun, Huan; Yan, Hui; Yuan, Yiwen; Peng, Yang; Tang, Xiangdong (Frontiers in Psychiatry, 2024)
Objectives This study aimed to investigate the psychological stress experienced by frontline medical staff during the Yangbi Earthquake and to understand how coping strategies and social support influence stress responses. Methods From days 3 to 14 post-earthquake, online questionnaires were administered to frontline medical staff to assess perceived social support, coping strategies, and psychological stress responses using the Perceived Social Support Scale (PSSS), Trait Coping Strategies Questionnaire (TCSQ), and Stress Response Questionnaire (SRQ). Data analysis included correlation analysis to explore relationships between variables, multiple linear regression to identify key predictors of stress, and path analysis to determine direct and indirect effects. Results A total of 253 valid questionnaires were analyzed, with a participant composition of 81.82% females and 18.18% males, and the majority being nurses (62.06%). Psychological stress responses varied by gender and age, with females and older age groups showing higher physical stress responses (P < 0.05). Correlation and regression analyses indicated that negative coping and lower levels of social support were associated with increased stress responses (P < 0.05). Path analysis revealed that intra-family and extra-family support influenced stress responses directly and indirectly through coping strategies (P < 0.05). Conclusion This study suggests that perceived social support directly influences stress responses in frontline medical personnel during disasters, with coping strategies mediating this effect. Future research should explore these dynamics over time through longitudinal studies.